Interactome Analysis of the ER Stress Sensor Perk Uncovers Key Components of ER-Mitochondria Contact Sites and Ca2+ Signalling. (November 2021) - Sassano, Maria Livia; Derua, Rita; Waelkens, Etienne; Agostinis, Patrizia; van Vliet, Alexander R
We recently reported that the ER stress kinase PERK regulates ER-mitochondria appositions and ER– plasma membrane (ER-PM) contact sites, independent of its canonical role in the unfolded protein response. PERK regulation of ER-PM contacts was revealed by a proximity biotinylation (BioID) approach and involved a dynamic PERK-Filamin A interaction supporting the formation of ER-PM contacts by actin-cytoskeleton remodeling in response to depletion of ER-Ca 2+ stores. In this report, we further interrogated the PERK BioID interactome by validating through co-IP experiments the interaction between PERK and two proteins involved in Ca 2+ handling and ER-mitochondria contact sites. These included the vesicle associated membrane (VAMP)-associated proteins (VAPA/B) and the main ER Ca 2+ pump sarcoplasmic/endoplasmic reticulum Ca ATPase 2 (SERCA2). These data identify new putative PERK interacting proteins with a crucial role in membrane contact sites and Ca 2+ signaling further supporting the uncanonical role of PERK in Ca 2+ signaling through membrane contact sites (MCSs).